2022
DOI: 10.1186/s12891-022-05134-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lateral femoral condyle ratio measured by MRI is associated with higher risk of noncontact anterior cruciate ligament injury

Abstract: Background Studies have shown a significant association between the radiographically measured lateral femoral condyle ratio (LFCR) and anterior cruciate ligament (ACL) injury. However, it is unclear whether LFCR measured by magnetic resonance imaging (MRI) is associated with a higher risk of noncontact ACL injury. Objective To investigate the effect of LFCR on the risk of noncontact ACL injury by MRI. 2 to investigate the association of LFCR measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In contrast, earlier studies reported that the mean locations for ACL femoral footprint centres were 23.8–37.3% in the DS direction and 26.6–44.3% in the HL direction [18]. In addition, previous studies indicated a position relative to the ADC ranged from 10.8 to 12.0 mm distally and 9.1 to 9.3 mm anteriorly [9, 18]. For the single‐bundle ACLR, Pearle et al .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, earlier studies reported that the mean locations for ACL femoral footprint centres were 23.8–37.3% in the DS direction and 26.6–44.3% in the HL direction [18]. In addition, previous studies indicated a position relative to the ADC ranged from 10.8 to 12.0 mm distally and 9.1 to 9.3 mm anteriorly [9, 18]. For the single‐bundle ACLR, Pearle et al .…”
Section: Discussionmentioning
confidence: 95%
“…For the BH grid method, Blumensaat’s line was first drawn along the roof of the intercondylar notch of the femur, as seen on the reformatted oblique‐sagittal plane. Subsequently, the coordinates of the ACL femoral footprint centre in the deep–shallow (DS) direction and the high–low (HL) direction were measured. Other anatomical features that have been reported to be associated with ACL injury, like notch shape, Blumensaat’s line type, notch width, condylar width, notch width index (NWI), notch height, condylar height, notch height index (NHI), α angle (°), β angle (°), the lateral femoral condyle ratio (LFCR) and the lateral femoral condyle index (LFCI), which previously reported as related to ACL injury, were evaluated according to the previous studies [9, 11, 24]. With Materialise’s Interactive Medical Image Control System software (Version 21.0, Materialise, Leuven, Belgium), the shape of the ACL femoral footprint was demonstrated on the 3D model through 3D reconstruction (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we included patients with only meniscal injury in the control group. Although this method has been widely adopted by previous studies [ 24 , 50 , 51 ], the inclusion of this population may introduce some bias.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been reported as the most reproducible for measuring lateral tibial slope and is independent of the length of proximal tibia [ 19 ]. To determine the most predictive bony morphological risk factors, the following parameters were also measured according to the original description: medial tibial depth (MTD) [ 20 ], lateral tibial height (LTH) [ 21 ], notch width index (NWI) [ 22 ] and lateral femoral condyle ratio (LFCR) [ 23 , 24 ] (Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%